Eleven Myths on Nail Melanoma - Eckart Haneke Eckart Haneke (European Medical Journal, 2021)
Tuberous sclerosis complex (TSC) is an autosomal dominant hereditary disease with hamartomatous growths in multiple organs due to loss-of-function variants in TSC1 or TSC2. In approximately 15% of patients with clinical TSC, no pathogenic variant can be identified, and low-level mosaicism is suggested to be one of the reasons. Mosaicism is well-known in TSC and challenges the molecular genetic diagnosis. The advent of next-generation sequencing has improved the diagnostics in TSC including in patients with mosaicism. The TSC phenotype varies widely, and mosaic patients with TSC are often considered to have a milder phenotype. Here, the authors describe a patient with mosaic TSC with a 10% variant allele fraction and manifestations in three organ systems (skin, eyes, and kidneys). Furthermore, the authors studied existing literature about phenotypic organ manifestations in patients with mosaic TSC. No clear definition of the phenotype of patients with mosaic TSC could be established, but unilateral angiofibromas and the absence of tubers and a subependymal nodule could indicate mosaicism. The case shows that patients with low-level mosaic TSC can have multiple affected organ systems though still a mild clinical picture.